Papers of Graeme Murphy and Janet Vernon - Murphy, Graeme, 1950-; Vernon, Janet (1976)
The collection comprises papers accumulated by Graeme Murphy and Janet Vernon during the course of their careers and association with the Sydney Dance Company. The records include correspondence; files relating to specific performances, projects, choreographic workshops, and master classes; original scenarios and scores for major productions; notes from dance classes; production notes; cast sheets; lists of tours; financial records; and press cuttings.
MS Acc08.088 includes papers relating to performances of Tivoli; Ainadamar; Mulan; Cut; Grand; The Directors Cut; Berlin; Ever After Ever; Turandot; and others.
Manuscript reference no.: MS Acc08.088.
National Library of Australia Oral History collection ORAL TRC 1/1222-1223.
National Library of Australia Oral History collection ORAL TRC 2680.
National Library of Australia Oral History collection ORAL TRC 3478.
National Library of Australia Oral History collection ORAL TRC 2650.
Dancers, choreographers and artistic directors, Graeme Murphy and Janet Vernon met as students at the Australian Ballet School in Melbourne in the 1960s. Murphy joined the Australian Ballet in 1968 and toured the United States with the Australian Ballet in 1970-1971. An Australia Council grant enabled him to study in New York. Murphy then worked with the Royal Ballet in London before joining Vernon in France, where she was performing with Les Ballets Félix Blaska. In 1976 Murphy was appointed artistic director of the Dance Company of New South Wales, which became the Sydney Dance Company in 1979. With Vernon as associate director, their creative collaboration with the Sydney Dance Company was to span 30 years. They built for the company a national and international reputation as a major contemporary dance company presenting over 140 original works, over half of which were created by Murphy. The company toured extensively both in Australia and overseas; showcased contemporary dance with works commissioned by national and international guest choreographers; staged choreographic workshop programs to develop the skills of its dancers; and commissioned scores from local composers. In 1985, the Sydney Dance company was honoured to be the first Western contemporary dance company to be invited to perform in China. Vernon and Murphy resigned from the Sydney Dance Company in July 2006.
Keywords: Murphy, Graeme, -- 1950- -- Archives; Vernon, Janet -- Archives; Sydney Dance Company -- Employees -- Archives; Ballet dancers -- Australia -- Archives; Choreographers -- Australia -- Archives; Modern dance -- Australia -- Archives; Ballet dancers; Choreographers; Artistic directors